Native arbuscular mycorrhizal fungal communities in trap cultures are shaped by traditional host plants and agricultural soils - Sakha, M.; Gweyi-Onyango, J.P.; Kaushal, M.; Baijukya, F.P.; Masso, C. (2025)
Arbuscular mycorrhizal (AM) fungi inoculants are increasingly recognized as effective biofertilizers in sustainable agriculture. Typically, as a first step for AM fungi inoculum production, a trap culture system using mycotrophic host plants is commonly used to isolate AM fungi. However, the influence of traditional host plants and agricultural field soil on the composition of AM fungal communities in trap cultures remains poorly understood. The greenhouse study was conducted to assess the sporulation capacity of AM fungi by applying a trap culture technique using traditional varieties endemic to the semi-arid areas of eastern Kenya as host plants, along with soils sourced from the same area. The traditional varieties used included Kinyaanya maize, Vaasya sorghum, and Katumbuka beans. Soil samples were collected from 34 agricultural fields. Trap culture pots were established and maintained in a greenhouse for 120 days. The experiment was set up in a completely randomized design. AM fungi spores were extracted using the wet-sieving and decanting method, and healthy spores were selected for morphological analysis. Across all three host plants and the control (original agricultural field soils), six AM fungal genera were identified: Acaulospora, Scutellospora, Gigaspora, Dentiscutata, Racocetra, and Funneliformis. Our results demonstrated that traditional host plants differentially influence AM fungal sporulation. Notably, trap cultures revealed AM fungal species that were not detected in the control. The abundance of AM fungal spores showed a weak correlation with soil chemical properties. Additionally, the Maize variety proved to be a more effective host for propagating AM fungal spores compared to the other crops evaluated. These findings suggest that further research is needed to determine whether the co-culturing of multiple traditional host plants is as effective as the monoculture cultivation of a single host plant for AM fungi propagation.